Representation of Money in Visual Advertising Visual Discourse Analysis of Mellat Bank Advertising Campaign - Maryam Kahvand (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
With the development of visual communication in the present age, the analysis and reading of visual texts in order to decipher the meanings and express their meanings is of particular importance. Critical discourse analysis, as one of the approaches that considers both the context of the text and the social context of the text, has made it possible to study discourses in works of art. The purpose of this paper is to introduce visual discourse or visuality as a way to analyze images, and its theoretical framework is dedicated to reviewing the critical visual methodology, which is an integrated model of Rose and Fairclough methodology. In the process of analysis, the Mellat Bank's advertising campaign has been visually criticized in order to elucidate its visual discourse based on the textual components of the images and the fields of its representation. The structure of technology, the configuration of images, and the social effects of visual components are discussed in the sites of the text, discourse action, and social action. The findings of the research indicate that the discourse function of this campaign is to highlight the value of money as national and cultural capital and to promote empathy and patriotism in the audience, during which the Mellat Bank changes its identity from a financial institution to a cultural institution.